Potensi Antimikroba Kunyit Putih (Curcuma ceasia) pada Edible Film Pati Sukun (Artocarpus altilis) - Nanik Suhartatik; Merkuria Karyantina; Crisdyana Eko Setyaningsih (LPPM Universitas Terbuka, 2022)
Breadfruit starch contains a relatively high number of amylose which has potency to be develop as edible film. It is also necessary to develop packaging materials which also contain natural antimicrobial compounds. White turmeric contains phytochemical compounds that have antimicrobial activity. This study aimed to determine the optimal concentration of breadfruit starch in edible films and to study the effect of white turmeric extract addition to inhibit the growth of Eschericia coli and Staphylococcus aureus. The study used factorial completely randomized design which consist of 2 factors and two fold replication, namely the concentration of breadfruit starch and the concentration of white turmeric extract. The results showed that breadfruit starch at 8% concentration produce good edible film with a tensile strength reach up to 4.57 Â± 0.135 MPa. Meanwhile the addition of 2.5% white turmeric could inhibit the growth of tested bacteria. Inhibition zone reached 1.38 cm for E. coli and 1.40 cm for S. aureus. White turmeric has the potency to be developed as a natural antimicrobial compound in breadfruit starch edible films.